2016
DOI: 10.1111/ijsa.12153
|View full text |Cite
|
Sign up to set email alerts
|

Status Seeking and Manipulative Self‐presentation

Abstract: Three studies examine the relation of dispositional status‐seeking with workplace self‐presentation behaviors. The first study showed that the status‐seeking motive provided incremental prediction, over and above narcissism and self‐monitoring, in self‐reported exaggerating, faking, and fabricating in job search. The second study showed that, after controlling for the traits from the five factor model of personality, status‐seeking predicted the undesirable job‐search behaviors, as well as use of impression‐ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…In terms of the “wanting more” aspect of greed, a higher social status is necessary given that resources are generally distributed according to one’s standing in the social hierarchy of the organization (Highhouse et al, 2016). The findings of the current study provide some empirical evidence that the greedier an individual is, the stronger his or her need for social status, and the higher his or her level of performance.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of the “wanting more” aspect of greed, a higher social status is necessary given that resources are generally distributed according to one’s standing in the social hierarchy of the organization (Highhouse et al, 2016). The findings of the current study provide some empirical evidence that the greedier an individual is, the stronger his or her need for social status, and the higher his or her level of performance.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in a series of studies, Flynn, Reagans, Amanatullah, and Ames (2006) showed correlations ranging between 0.25 and 0.31 with need for social status, and supported the hypothesis that self-monitoring was related to social status as mediated by perceived generosity. Similarly, Highhouse, Brooks, and Wang (2016) found a correlation of 0.28 between self-monitoring and statusseeking. Interestingly, even though self-monitoring is related to status seeking, its relationship with need for approval follows a different pattern.…”
Section: Introductionmentioning
confidence: 90%
“…Similarly, in a lab study of faking during job interviews, Hogue, Levashina, and Hang (2013) concluded that self-monitoring was related to intentions toward mild, but not severe faking. Highhouse et al (2016) showed that self-monitoring predicted fabricating one's credentials as part of the job search. Finally, self-monitoring was negatively associated with integrity ratings in assessment centers (Leugnerova, Vaculik, & Prochazka, 2016).…”
Section: Self-monitoring and The Employee Selection Processmentioning
confidence: 99%
“…Hewlin, 2009) and appear to believe in the images they project of themselves (Snyder, 1987; Gangestad and Snyder, 2000; Kudret et al , 2019). Such an impression management motivation is primarily charged by their need to act appropriately in social situations and seek social status (Highhouse et al , 2016; Kudret et al , 2019).…”
Section: Background and Hypotheses Developmentmentioning
confidence: 99%